Anthropometric measures and bladder cancer risk: A prospective study in the EPIC cohort. Issue 12 (6th May 2014) - Roswall, Nina; Freisling, Heinz; Bueno‐de‐Mesquita, H. B(as); Ros, Martine; Christensen, Jane; Overvad, Kim; Boutron‐Ruault, Marie‐Christine; Severi, Gianluca; Fagherazzi, Guy; Chang‐Claude, Jenny; Kaaks, Rudolf; Steffen, Annika; et al.
<x xml:space="preserve">Abstract</x> Anthropometric measures have been related to risk of several cancers. For bladder cancer, however, evidence is sparse. Comparability of existing studies is hampered by use of different obesity‐measures, inadequate control for smoking, and few female cases. This study examined associations between height, weight, waist and hip circumference, waist–hip ratio, waist–height ratio, body mass index (BMI), recalled weight at age 20 and bladder cancer, and investigated effect modification by age, tumor aggressiveness and smoking. The study was conducted in the European Prospective Investigation into Cancer and Nutrition cohort, in 390, 878 participants. Associations were calculated using Cox Proportional Hazards Models. During follow‐up, 1, 391 bladder cancers (1, 018 male; 373 female) occurred. Height was unrelated to bladder cancer in both genders. We found a small but significant positive association with weight [1.04 (1.01–1.07) per 5 kilo], BMI [1.05 (1.02–1.08) per 2 units], waist circumference [1.04 (1.01–1.08) per 5 cm], waist–hip ratio (1.07 (1.02–1.13) per 0.05 unit] and waist–height ratio [1.07 (1.01–1.13) per 0.05 unit] in men. Stratification by smoking status confined associations in men to former smokers. In never smokers, we found no significant associations, suggesting residual confounding by smoking. Results did not differ with tumor aggressiveness and age. Residual analyses on BMI/waist circumference showed a significantly higher disease risk with BMI in men (p = 0.01), but no association with waist circumference. In conclusion, in this large study, height was unrelated to bladder cancer, whereas overweight was associated with a slightly higher bladder cancer risk in men. This association may, however, be distorted by residual confounding by smoking.